2019
DOI: 10.1007/s11605-018-3830-x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Rectal Cancer Patients’ Decisions on Where to Receive Surgery: a Qualitative Analysis

Abstract: Most rectal cancer patients in our sample relied on physician referrals to decide where to receive surgery. Interventions facilitating more informed decision-making by patients and referring providers may be warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Despite these difficulties, our participants believed that a hospital volume-outcome relationship exists for TKA. Similarly, in other studies in the USA, participants believed that the number of times a surgeon performs rectal cancer surgery makes a difference to the outcomes [41], and candidates for hip or knee arthroplasty cared about hospital volume when deciding where to have surgery [26]. In Germany, patients ranked 'volume of specified surgical procedures' in 7th place out of 29 quality indicators [42], suggesting that hospital volume was perceived as important for outcome quality.…”
Section: Hospital Volumes and The Hospital Volume-outcome Relationshipmentioning
confidence: 86%
See 2 more Smart Citations
“…Despite these difficulties, our participants believed that a hospital volume-outcome relationship exists for TKA. Similarly, in other studies in the USA, participants believed that the number of times a surgeon performs rectal cancer surgery makes a difference to the outcomes [41], and candidates for hip or knee arthroplasty cared about hospital volume when deciding where to have surgery [26]. In Germany, patients ranked 'volume of specified surgical procedures' in 7th place out of 29 quality indicators [42], suggesting that hospital volume was perceived as important for outcome quality.…”
Section: Hospital Volumes and The Hospital Volume-outcome Relationshipmentioning
confidence: 86%
“…Referring physicians, as trusted experts and possible multipliers, could increase both awareness and understanding of information on hospital quality and volumes if they discussed it with their patients. This suggestion is supported by the finding that, in contrast to low volume hospitals, patients with rectal cancer in high volume hospitals received the recommendation for such hospitals from their social networks, such as referring physicians or relatives with medical knowledge [41]. However, older studies show that not all physicians are aware of hospital quality reports (48% of surveyed German physicians in 2010 [59]) and that few use such reports for referral and counselling of patients (approximately 12-20%) [59][60][61][62][63][64].…”
Section: Referring Physiciansmentioning
confidence: 90%
See 1 more Smart Citation
“…Our finding of infrequent referral of patients by individual physicians is consistent with the study of Mandl et al, who showed that collaboration of patient care among all types of providers for outpatient clinic appointments was uncommon [17]. Our focus on the referring physician in the context of the treatment of a brain tumor seems appropriate based on the study of Charlton et al, who demonstrated that most rectal cancer patients relied on the advice of their own physician, and few attempted to assess either surgeon volume or experience in deciding where to seek definitive treatment [18]. Our finding that a substantive number of patients (e.g., from Miami-Dade, Palm Beach, and Broward counties) drove past many other hospitals offering brain surgery or traveled to Miami (e.g., from Collier and Lee counties) rather than to closer hospitals in the opposite direction is consistent with the study of Dexter et al, who showed that absolute distance rather than relative distance was the important travel consideration [19].…”
Section: Discussionmentioning
confidence: 99%
“…The survey instrument was designed based on qualitative information collected from individuals diagnosed with rectal cancer in semistructured interviews. [19][20][21] Survey instruments were further vetted and refined based on feedback from colorectal surgeons and survey methodologists. Cognitive testing of the instrument was conducted with 5 individuals diagnosed with rectal cancer who had follow-up appointments for their rectal cancer surgery at a tertiary referral hospital in the month preceding survey implementation.…”
Section: Survey Instrument Designmentioning
confidence: 99%